2006
DOI: 10.1002/cmdc.200500029
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antitumor Activity of Clitocine, an Exocyclic Amino Nucleoside Isolated from Lepista inversa

Abstract: A biologically guided fractionation from Lepista inversa (Scop.: Fr.) led to the isolation of clitocine, an exocyclic amino nucleoside. This compound and two mixtures of beta/alpha anomers (mixture A, 40:60 and mixture B, 80:20) were synthesized or isolated depending on the purification procedure. The beta anomer and clitocine mixtures A and B showed similar cytotoxic activities with IC50 values ranging from 20.5 to 42 nM in murine cancer cell lines (3LL and L1210) and from 185 to 578 nM in human cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 16 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Clitocine, a nucleoside firstly isolated from the mushroom Clitocybe inversa in 1980s, was found to be a substrate and inhibitor of adenosine kinase [25]. Recent years, clitocine was reported to exert an anti-tumor effect in varies cancer cell lines such as Hela and MCF-7 cells, and many derivatives of this compound were also synthesized and examined for their biological properties [25], [26], [27], [28]. In the present study, we found that clitocine reverse the P-gp associated multidrug resistance in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Clitocine, a nucleoside firstly isolated from the mushroom Clitocybe inversa in 1980s, was found to be a substrate and inhibitor of adenosine kinase [25]. Recent years, clitocine was reported to exert an anti-tumor effect in varies cancer cell lines such as Hela and MCF-7 cells, and many derivatives of this compound were also synthesized and examined for their biological properties [25], [26], [27], [28]. In the present study, we found that clitocine reverse the P-gp associated multidrug resistance in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example illudin, a tricyclic sesquiter-pene from Omphalotus olearius, has served as the lead structure for the semisynthetic drug irofulven, which is currently in preclinical and clinical trials due to its effects against cancer-related kinases and apoptotic activity against a range of tumors (Baekelandt 2002). Cordycepin, isolated from several Cordyceps species, has shown an apoptotic effect on various cancer cell lines ( Jin et al 2008, Wu et al 2007 while the cytotoxicity of Lepista species has been attributed to the clitoclines (Fortin et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Fortin and coworkers isolated clitocine fractions in various a/b ratios from Lepista inverse -the pure b-anomer clitocine, mixture A (a/b ¼ 60 : 40), and mixture B (a/b ¼ 20 : 80) [7]. Interestingly, all of these fractions exhibited similar cytotoxic activities, with IC 50 values ranging from 20.5 to 42 nM in murine cancer cell lines (3LL and L1210), and from 185 to 578 nM in human cancer cell lines (DU145, K-562, MCF7, and U251).…”
Section: Biological Activitymentioning
confidence: 99%